Mechanical Performance Enhancement of Self-Decoupling Magnetorheological Damper Enabled by Double-Graded High-Performance Magnetorheological Fluid - Fei Guo; Hanbo Cui; Xiaojun Huang; Chengbin Du; Zongyun Mo; Xiaoguo Lin (Applied Sciences)
Conventional magnetorheological fluids (MRFs) exhibit a constrained shear strength that restricts their deployment in high-performance damping systems. This study introduces a dual-axis innovation strategy combining material science and device physics to fundamentally redefine MRF capabilities. We develop a hierarchical particle architecture through the controlled integration of micro/nano-sized carbonyl iron particles (CIPs), enhanced by polyethylene glycol/oleic acid surface engineering to optimize magnetic chain formation and interfacial bonding. The engineered MRF demonstrates a shear yield strength of 99.6 kPa at 0.757 T, surpassing conventional single-component MRFs by a significant margin. Integrated with a self-decoupling damper that isolates magnetic flux from mechanical motion, this synergistic design achieves exceptional force modulation: damping forces scale from 281.5 kN (5 mm stroke) to 300 kN (60 mm stroke), with current-regulated adjustability factors reaching 3.34. The system exhibits substantial improvements in both maximum damping force (93.9 kN enhancement) and energy dissipation efficiency compared to standard MRF dampers. Through co-optimization of the particle architecture and magnetic circuit design, this work establishes new performance benchmarks for smart fluid technology. The achieved force capacity and dynamic response characteristics directly address critical challenges in seismic engineering and industrial vibration control, where extreme load-bearing requirements demand simultaneous high strength and tunable damping capabilities.